Digital communications. - Glover, Ian A., ....-; Grant, Peter M., ....- (Harlow : Pearson, 2004)
1. Digital Communications Overview I. SIGNALS AND SYSTEMS THEORY 2. Periodic and Transient Signals 3. Random Signals and Noise 4. Linear Systems II. DIGITAL COMMUNICATIONS PRINCIPLES 5. Sampling, Multiplexing, and PCM 6. Bandbased Transmission and Line Coding 7. Decision Theory 8. Optimum Filtering for Transmission and Reception 9. Information Theory and Source Coding 10. Error Control Coding 11. Bandpass Modulation of a Carrier Signal 12. System Noise and Communications Link Budgets 13. Communication Systems Simulations III. APPLICATIONS 14. Fixed Point Microwave Communications 15. Mobile and Cellular Radio 16. Video Transmission and Storage IV. NETWORKS 17. Queuing Theory for Packet Networks 18. Network Topology and Protocols 19. Public Networks and the Integrated Services Digital Network (ISDN)
Keywords: Digitale telecommunicatie